Interactive computation in power system analysis - Undrill, J.M.; DeMello, F.P.; Kostyniak, T.E.; Mills, R.J. (Proceedings of the IEEE, 1974)
The analysis of power system performance has always been enhanced by close interaction between engineer and computation, and recent developments in high-speed displays, minicomputer capacity, and computational technology are encouraging major revisions of computing practices for power system analysis. A comprehensive power system analysis package, PSS/2, is described which has been developed specifically for use with dedicated computers. This dedicated computer approach allows load flow, short-circuit, and dynamic simulation work, data base maintenance, and printed report preparation to be handled in the interactive mode at lower cost than could be possible by alternative batch or time-shared computing methods. The subjects covered are data organization, computational techniques, user interface, and operational experience.